Assessing effects on dendritic arborization using novel Sholl analyses - O'Neill, Kate M.; Akum, Barbara F.; Dhawan, Survandita T.; Kwon, Munjin; Langhammer, Christopher G.; Firestein, Bonnie L. (Frontiers in Cellular Neuroscience, 2015)
Determining the shape of cell-specific dendritic arbors is a tightly regulated process that occurs during development. When this regulation is aberrant, which occurs during disease or injury, alterations in dendritic shape result in changes to neural circuitry. There has been significant progress on characterizing extracellular and intrinsic factors that regulate dendrite number by our laboratory and others. Generally, changes to the dendritic arbor are assessed by Sholl analysis or simple dendrite counting. However, we have found that this general method often overlooks local changes to the arbor. Previously, we developed a program (titled Bonfire) to facilitate digitization of neurite morphology and subsequent Sholl analysis and to assess changes to root, intermediate, and terminal neurites. Here, we apply these different Sholl analyses, and a novel Sholl analysis, to uncover previously unknown changes to the dendritic arbor when we overexpress an important regulator of dendrite branching, cytosolic PSD-95 interactor (cypin) at two developmental time points. Our results suggest that standard Sholl analysis and simple dendrite counting are not sufficient for uncovering local changes to the dendritic arbor.